Chemical Bonding Effect on the Incorporation and Conduction of Interstitial Oxide Ions in Gallate Melilites. Issue 9 (24th June 2019) - Xu, Jungu; Li, Yanchang; Zhou, Lijia; Tang, Xin; Kuang, Xiaojun
Abstract: The ability to incorporate high content of interstitial oxygen ions (Oi ) in La1+ x Sr1‐ x Ga3 O7+0.5 x melilite owing to the good size match between La 3+ and Sr 2+ ions is well documented. Here, the complete substitution of Sr 2+ by Pb 2+ lone‐pair cations results in a significant loss of this ability, even though Sr 2+ and Pb 2+ have almost the same effective ionic radius. To explore the fundamental mechanism underlying this result, density functional theory (DFT) calculations are performed on both the LaSrGa3 O7 ‐based and LaPbGa3 O7 ‐based materials, revealing a new chemical bonding effect on the incorporation of mobile oxygen interstitial defects in melilites. For LaSrGa3 O7 ‐based melilites, the interstitial oxygens have cooperatively weak antibonding interactions with the framework oxygen atoms (Of ). This antibonding Oi ‐Of interaction pushes Oi toward a 3‐linked Ga ion, enhancing the covalent bonding between this Ga ion and Oi . In addition, the antibonding Oi –Of interaction makes the oxygen interstitial defects and framework atoms highly active, benefiting the migration of defects. In contrast, for LaPbGa3 O7 ‐based materials, the 6s 2 electrons of Pb 2+ point toward the c ‐axis and form antibonding with framework O 2− . This antibonding projects into the tunnel void, thereby directly hindering the entrance of interstitial oxygen atoms into the pentagonal rings. Abstract : Chemical bonding is revealed to be a new factor controlling the incorporation and conduction of interstitial oxygens in gallate melilite . Antibonding Oi ‐Of interaction in LaSrGa3 O7 ‐based melilites makes the interstitial and framework oxygens highly active, while in LaPbGa3 O7 ‐based melilites, the antibonding interaction between the lone pair 6s 2 electrons of Pb 2+ and the framework O 2− hinders the incorporation of interstitial oxide ions.